Balancing the Interests of Justice: The Case of Afghanistan in The International Criminal Court (ICC) - Siti Rochmah Aga Desyana; Diajeng Wulan Christianti; Chloryne Trie Isana Dewi (Faculty of Law, Universitas Padjadjaran, 2021)
The interests of justice are criteria of the requirements under Article 53 of the Rome Statute to open a formal investigation of a case. However, it can be misinterpreted due to its lack of clear scopes and standards. The Afghanistan case highlighted this obscurity when The Pre-Trial Chamber (PTC) decided that the case should not proceed due to the interests of justice despite lacking negative determination from the Prosecutor, and the Appeals Chamber (AC) overturned this decision by excluding the interests of justice from proprio motu cases. This article verifies the limitations of the criteria in international criminal law (ICL) through the interpretation of the Rome Statute. In addition, it includes the other ICC’s supporting documents and the application to previous cases. This study is of the position that, in the Afghanistan decision, the PTC had overstepped their authority and made an arbitrary decision. The AC had misinterpreted the conjunction between Article 53(3) and Article 15(4) by excluding requirements under Article 53 from proprio motu cases. Based on the opinion, the interpretation on the interests of justice to ensure the criteria still valid as a balancing mechanism under the Rome Statute is very urgent. Menyeimbangkan Kepentingan Keadilan: Studi Putusan Pra-Peradilan dan Banding Mahkamah Pidana Internasional untuk Kasus Afghanistan AbstrakKepentingan keadilan adalah salah satu kriteria dalam Pasal 53 Statuta Roma tentang pembukaan penyidikan kasus. Akan tetapi, kriteria ini sangat mungkin untuk disalahgunakan karena kurangnya kejelasan akan cakupan dan standarnya. Kasus Afghanistan adalah contoh hasil produk dari ketidakjelasan ini. Kamar pra-Peradilan (KPP) memutuskan untuk tidak melanjutkan kasus ini karena melawan kepentingan keadilan meskipun Jaksa menyatakan bahwa kepentingan keadilan telah terpenuhi. Kemudian, Kamar Banding (KB) membatalkan putusan tersebut dengan menyatakan bahwa kepentingan keadilan dalam Pasal 53 tidak seharusnya dipertimbangkan dalam kasus proprio motu. Tulisan ini menganalisis batasan dari kepentingan keadilan dalam hukum pidana internasional dengan mengkaji keberadaannya di hukum domestik dan perspektif Mahkamah Pidana Internasional dalam memaknainya. Melalui kajian ini, ditemukan bahwa KPP telah melangkahi kewenangan mereka dan membuat keputusan tak berdasar pada kasus Afghanistan, dan KB salah memaknai hubungan antara Pasal 53(1) dan Pasal 15(4) Statuta Roma dalam putusannya. Karena pentingnya kriteria kepentingan keadilan, penting untuk segera memberikan penafsiran yang baku agar kriteria tersebut dapat digunakan tanpa melanggar Statuta Roma.Kata kunci: Afghanistan, kepentingan keadilan, Statuta Roma.DOI: https://doi.org/10.22304/pjih.v8n1.a6